2008
DOI: 10.1016/j.ejcts.2008.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of mediastinitis using video-assisted thoracoscopic surgery

Abstract: Mediastinal drainage using video-assisted thoracoscopic surgery with or without cervical drainage can be a feasible and effective surgical option. This less invasive technique seems to have an outcome similar to more aggressive open surgical approaches for patients with mediastinitis previously reported in the literature, although it has not been directly compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 18 publications
1
27
0
5
Order By: Relevance
“…In their series, all patients that underwent both cervicotomy and thoracotomy survived. More recently, less invasive approaches successfully employing thoracoscopic or mediastinoscopic drainage have been reported [11,14,[48][49][50][51][52][53][54][55].…”
Section: Review: Descending Necrotising Mediastinitis E Weaver Et Almentioning
confidence: 99%
“…In their series, all patients that underwent both cervicotomy and thoracotomy survived. More recently, less invasive approaches successfully employing thoracoscopic or mediastinoscopic drainage have been reported [11,14,[48][49][50][51][52][53][54][55].…”
Section: Review: Descending Necrotising Mediastinitis E Weaver Et Almentioning
confidence: 99%
“…Authors advocating the use of median sternotomy claim the wide exposure of the infection area as an advantage, whiles authors opposing the use of sternotomy claim the risk of sternal osteomyelitis and insufficient exposure of the posterior basal area of the left hemithorax [14]. There is literature reporting the Desendan Nekrotizan Mediastinit / Descending Necrotizing Mediastinitis use of minimal invasive approach of thoracoscopic surgery to be enough and applicable in the treatment of DNM [15]. In our clinical experience thoracotomy was superior over thoracoscopic surgery in terms of mechanical debridement, and with thoracotomy the expected complete mediastinopleural connection was established after failure with thoracoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…13 With regard to minimally invasive surgery, two recently published studies are of particular interest, given that they examine VATS as a treatment for ANM14 (with a mortality rate of 16.7%), and for mediastinitis caused by oesophageal perforation, also performing the oesophageal repair using VATS. 9 We don't have enough VATS experience for treat this urgent pathology with minimal invasion, but, in expert hands it can be a proper treatment with good results published. 6,10 One of the factors influencing survival is the time passed between onset of symptoms and diagnosis, with late diagnosis being related to lower survival rates: 13,15 in the present series it can be observed that patients diagnosed beyond the initial 24 h have half the chance of survival as those diagnosed before.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, posterolateral thoracotomy is carried out in order to drain the mediastinal cavity, although some recent published studies report a minimally invasive approach using videothoracoscopy 6,9 in cases of ANM and even oesophageal perforations. In patients for whom the origin of the mediastinitis is buccocervical, the cervical approach with widereaching debridement appears to be crucial and in cases of oesophageal origin, it is essential to repair the oesophagus.…”
Section: Discussionmentioning
confidence: 99%